Pengembangan Kreativitas Berbasis Kepribadian pada Anak Usia Dini - Dedy Surya (Aṭfāluna: Journal of Islamic Early Childhood Education, 2018)
One of the purposes in early childhood education is to guard the development of the children's creativity development and to maximize the potential possessed accordingly with the age. The Well-developed creativity will become very important because with creativity, in the future the children will able to think about something with a different perspective, to find something new, and to solve various problems differently. This article is to build the awareness of teacher in early childhood education to participate in the personality of children as a student in order to determine exactly the development strategy and the most effective method the most effective way to maximize the creativity they have.